The Effect of Mabar Applications on Improving Knowledge of Out Hospital Cardiac Arrest among High School Students - Susmini; Wahyu Dwi Ari WIbowo; Sapondra Wijaya; Nindya Amelia (Alta Dharma Publisher, 2021)
Introduction: Out-of-hospital cardiac arrest (OHCA) is one of the major contributors to mortality in the world. It is important to encourage knowledge of cardiac arrest management for everyone. Objective: This study aimed to examine the effect of Mabar applications on improving knowledge of cardiac arrest management among students. Method: The True Experimental study, pre-test, and post-test with non-equivalent control group design was applied in this study. Results: The result found that there is a significant improving knowledge between before and after training CPR from the simulation method (p <0.05), MABAR application (p <0.05), However, the comparison both of methods showed a significant difference in knowledge after receiving training p = 0.01 (p <0.05). All of the methods have an influence on increasing knowledge before and after training CPR. However, the Mabar application was effective to improve more clinical skills, saving time and energy. It has compatible with using independently without depending on the trainer. Using Mabar applications can increase attention and impulse for the trainer. Recommendation: The Mabar application as a CPR training method is highly recommended, especially for teenagers and students. For further research need to examine this application for a wide population